2004
DOI: 10.1016/j.jvs.2003.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and social consequences of buerger disease

Abstract: The natural course of life and limb is favorable in many patients with Buerger disease. Occurrence or recurrence of necrotic lesions usually is arrested in patients older than 60 years. To avoid factors that markedly influence quality of life, early treatment and strict instruction to prohibit smoking are mandatory. Arterial reconstruction shortens the healing process of ischemic ulcers, despite poor long-term results. However, bypass surgery to treat intermittent claudication should be limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
107
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(130 citation statements)
references
References 7 publications
4
107
0
6
Order By: Relevance
“…Although successful bypass surgery dramatically improves symptoms of ischemia, it has poor long-term results and is not frequently applicable in the case of Buerger's disease. The results of arterial reconstruction using UCB-derived MSCs were better than others reported by Ohta et al and Sasajima et al [5,24]. This study showed that arterial reconstruction or prevention of arterial obstruction using UCB-derived MSCs completely controls the rest pain and shortens the healing process of ischemic ulcers.…”
Section: Discussionsupporting
confidence: 47%
“…Although successful bypass surgery dramatically improves symptoms of ischemia, it has poor long-term results and is not frequently applicable in the case of Buerger's disease. The results of arterial reconstruction using UCB-derived MSCs were better than others reported by Ohta et al and Sasajima et al [5,24]. This study showed that arterial reconstruction or prevention of arterial obstruction using UCB-derived MSCs completely controls the rest pain and shortens the healing process of ischemic ulcers.…”
Section: Discussionsupporting
confidence: 47%
“…Taking TAO cases as an example, these patients represent the vast majority of AICLI patients and can be treated by many methods, including surgical bypass, endarterectomy, embolectomy, sympathectomy, superficial vein arterialization, PTA, thrombolysis, and stenting; however, none of these methods provide ideal mid‐ to long‐term efficacy. Without cell therapy, the major amputation rate of TAO patients, including CLI and claudicants, has been reported to be as high as 12%–31% 20, 21, 22. Ohta et al observed that 118 TAO patients presented a total major amputation rate of 19%; moreover, this study revealed that the primary patency rates of the surgical bypass subgroup were 41% (1 year), 32% (5 years), and 30% (10 years), respectively, and the secondary patency rates of this group were 54% (1 year), 47% (5 years), and 39% (10 years), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Complete abstinence from smoking is critical for success of available therapy [2,12]. Early treatment is also important to avoid social problems and improve quality of life [17].…”
Section: Discussionmentioning
confidence: 99%